2015
DOI: 10.1016/j.neuron.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Pathways from the Ventromedial Hypothalamus Mediate Defensive Behaviors

Abstract: Summary The ventromedial hypothalamus (VMH) was thought to be essential for coping with threat, although its circuit mechanism remains unclear. To investigate this, we optogenetically activated steroidogenic factor 1 (SF1)-expressing neurons in the dorsomedial and central part of VMH (VMHdm/c), and observed a range of context dependent somatomotor and autonomic responses resembling animals' natural defensive behaviors. By activating independent pathways emanating from VMHdm/c, we demonstrated that VMHdm/c proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
261
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(300 citation statements)
references
References 45 publications
22
261
2
1
Order By: Relevance
“…Together, this and our results show that the dPAG is necessary and sufficient to induce defensive behavior. Intriguingly, it is reported that optogenetic activation of the ventromedial hypothalamus (VMH)-dorsolateral PAG pathway produces immobility, but not flight or avoidance (Wang et al, 2015). Given that the induction of flight or avoidance may require additional threat inputs that are not provided by the VMH, the behavioral effect of VMH-PAG pathway activation should be further tested in the presence of a live predator or a predatory odor.…”
Section: Discussionmentioning
confidence: 99%
“…Together, this and our results show that the dPAG is necessary and sufficient to induce defensive behavior. Intriguingly, it is reported that optogenetic activation of the ventromedial hypothalamus (VMH)-dorsolateral PAG pathway produces immobility, but not flight or avoidance (Wang et al, 2015). Given that the induction of flight or avoidance may require additional threat inputs that are not provided by the VMH, the behavioral effect of VMH-PAG pathway activation should be further tested in the presence of a live predator or a predatory odor.…”
Section: Discussionmentioning
confidence: 99%
“…These three highly interconnected nuclei are selectively recruited by predator exposure (and not by conspecific threat or pain), receive inputs from sensory circuits detecting predatory cues, and target defense output structures like the PAG (Canteras 2002). Accordingly, inhibition of these nuclei impairs defensive responses to predators while their artificial activation promotes defensive responses in both rodents and primates (Lipp and Hunsperger 1978;Canteras et al 1997;Blanchard et al 2005;Wilent et al 2010;Pavesi et al 2011;Silva et al 2013;Kunwar et al 2015;Wang et al 2015).…”
Section: The Predator Fear Circuitmentioning
confidence: 99%
“…For example, blockade of the VMHdm or PMD impairs freezing, avoidance, escape, risk assessment, anxiety, and autonomic responses (Blanchard et al 2003Silva et al 2013;Cheung et al 2015;Kunwar et al 2015), while optogenetic activation of the VMHdm induces flights, freezing, autonomic activation, and the interruption of ongoing behaviors (Lin et al 2011;Kunwar et al 2015;Wang et al 2015). Interestingly, VMH activation seems to evoke defensive behaviors in a scalable fashion, with less intense stimulation inducing freezing and more intense stimulation evoking activity bursts (Kunwar et al 2015).…”
Section: Mhds Induction Of Multiple Defensive Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations